2018
DOI: 10.1016/j.nefro.2017.04.003
|View full text |Cite
|
Sign up to set email alerts
|

The role of bioelectrical impedance analysis, NT-ProBNP and inferior vena cava sonography in the assessment of body fluid volume in children with nephrotic syndrome

Abstract: Our findings support the lack of hypovolaemia in NS during acute attack. In addition, BIA is an easy-to-perform method for use in routine clinical practice to determine hydration status in patients with NS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 37 publications
1
6
0
2
Order By: Relevance
“…In the present study, BIS clearly indicated a higher ECW in the ANS patients compared to both the controls (HC group) and patients at remission (NSR group). Importantly, these findings accord with observations made in previous studies in NS patients [4, 25], where absolute fluid volumes were estimated using predictive methods.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In the present study, BIS clearly indicated a higher ECW in the ANS patients compared to both the controls (HC group) and patients at remission (NSR group). Importantly, these findings accord with observations made in previous studies in NS patients [4, 25], where absolute fluid volumes were estimated using predictive methods.…”
Section: Discussionsupporting
confidence: 91%
“…BIS has recently been used to demonstrate increased volumes of extracellular water (ECW) in NS patients compared to controls [4]. As well as being able to provide information about the volume of the different body water compartments, BIS also estimates cell membrane capacitance (C M ), which has been suggested as the parameter directly linked to the cell membrane function [5]; low C M has been linked to disease in children [6].…”
Section: Introductionmentioning
confidence: 99%
“…Some authors consider multifrequency bioimpedance technology as a promising approach in body water compartment estimation [13,17,25]. In recent years, data obtained by its application in dialyzed children and adolescents and in pediatric nephrotic syndrome have been reported [16,42]. Using multifrequency bioimpedance, we identified that OH, ECW/ICW, and ECW/TBW were increased in the HD and PD groups compared with the control group.…”
Section: Discussionmentioning
confidence: 89%
“…However, data regarding the usage of bioelectrical impedance in nephrotic syndrome is limited. So far, bioimpedance technology has been used to estimate the fluid status of patients with nephrotic syndrome rather than body composition [ 18 21 ]. We decided to use this method to compare body composition in different groups of patients with kidney disease as simple tool which can be used at the patients’ bedside.…”
Section: Discussionmentioning
confidence: 99%